Edukasi Remaja Sadar Gizi Untuk Pencegahan Kekurangan Energi Kronik (KEK) Dalam Menurunkan Angka Kematian Ibu (Aki) di Praktek Mandiri Bidan Dewi Ciselia - Ciselia, Dewi; Sari, Yona; Ariyani, Yulinda (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
Chronic Energy Deficiency (KEK) is a state of malnutrition, Pathological due to a relative or absolute deficiency or excess of one or more nutrients, and the measurement results of the lila are less than 23.5 cm.  According to data from the World Health Organization (WHO) in 2017, the maternal mortality rate throughout the world is estimated at 210/100,000 live births and the neonatal mortality rate has decreased by 38%, namely 36/1000 births. Of all maternal deaths, this is severe bleeding, generally bleeding after childbirth, postpartum infections. , high blood pressure during pregnancy (preeclampsia and eclampsia).  The aim of this activity is to provide nutrition awareness education for teenagers to prevent chronic energy deficiency (KEK). The method for implementing this Community Service Program is community education in the form of health education, evaluated with a pre-test and post-test. The method for implementing the community service is by providing nutrition-aware youth education by means of discussions using ebooklet media about balanced nutrition and KEK. The number of participants who attended was 50 people, 2 students, and 5 midwives. Activities start from the planning, implementation, evaluation, to report preparation stages. As a result of the activity, there was a change in knowledge with an average pre-test of 90.5% of participants' knowledge being in the poor category and post-test results of 95.5% being in the good category. In the skills aspect, all participants present (100%) were able to understand nutritional awareness to prevent CED. Conclusion. Educational activities about nutritional awareness for the prevention of CED can be an effort to increase knowledge and promote nutritional health in the prevention and control of CED. It is hoped that this activity can become a health promotion strategy in preventing and controlling SEZ